Analisis Butir Soal Ulangan Semester Genap Bahasa Indonesia Kelas IV SDN 51 Buton - Muhammad Yusnan; WD Nahda Aulia G; Tria; Nilam Sari (HAMJAH DIHA FOUNDATION bekerjasama dengan PENA INSTITUTE, 2025)
Evaluation is one of the most important components of learning, as it serves as a means to assess students’ abilities and achievements. In developing assessment tools, item analysis must be conducted to ensure the quality of the test items. This study aims to analyze the quality of the end-of-semester test items for Grade IV Indonesian Language subject in the 2024/2025 academic year, based on item difficulty level and discrimination index. This research is a quantitative descriptive study. Data collection was conducted through documentation of the Grade IV Indonesian Language end-of-semester test. The collected data were used to determine the quality and feasibility of the test items. The population of this study includes all items in the 2024/2025 Indonesian Language end-of-semester test at SDN 51 Buton. The sample consisted of the Grade IV test items, with a total of 17 students in the class. The results show that: (1) in terms of difficulty level, 9 items (45%) were categorized as easy, 11 items (55%) as moderate, and 0 items (0%) as difficult; (2) in terms of discrimination index, 2 items (8%) were categorized as very good, 8 items (42%) as good, 8 items (42%) as fair, and 2 items (8%) as poor. Overall, the quality of the Indonesian Language test items for the 2024/2025 academic year at SDN 51 Buton can be considered good, although improvements are still needed for several items to enhance the overall test quality. Therefore, item analysis based on difficulty level and discrimination index is essential to develop better test items in the future.